Le développement du media de la bande dessinée digitale pour la compréhension écrite en classe dix au premier semestre - Sunu Tri Pratama; Diah Vitri Widayanti (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2024)
There are four basic skills in learning the French language, one of these skills is reading comprehension. Reading comprehension is one of the skills that students must master. French is a language that is starting to be taught in high school; students need media that can help them understand French texts. Based on the needs analysis results, teachers and students agree that learning media is developed in the form of digital comics. This research aims to develop digital comic media to help students to understand French texts. This research uses the Research and Development methods (R&D) that adapt five steps: 1) potential and problem, 2) data collection, 3) product creation, 4) product validity, and 5) product revision. This research results in the digital comic media for reading comprehension in class ten of the first semester. There are four materials contained in this media: 1) greet and say goodbye, Say thank you and apologize, 2) introduce yourself, 3) hour, day, date, month, year, and 4) present your identity. In this digital comic media, there are four parts: basic competency and indicators, comics, speech act, vocabulary, and evaluation.